Investigation on the microstructure, microhardness, and tribological behavior of AA1100-hBN surface composite - Premkumar, R.; Vignesh, R. V.; Padmanaban, R.; Govindaraju, M.; Santhi, R. (Korose a ochrana materiálu, 2021)
Aluminum alloy AA1100 has less wear resistance and mechanical properties than that of other aluminum alloys. This research work is on the fabrication of surface composites of AA1100 alloy by friction stir processing (FSP). The surface composites are fabricated by reinforcing hBN (hexagonal Boron Nitride) in AA1100 alloy to improve the mechanical and tribological properties. The influence of process parameters, rotational speed (rpm), and transverse speed (mm/min) on the microstructural evolution and properties of the fabricated surface composites is investigated.